Didactic Experiments of Andrii Vvedens’kyi - Бездрабко, Валентина (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
Scientific and pedagogical creative heritage of professor of historical science A. Vvedens’kyi was considered from historical and historiographical points. We have made the general remarks about the dependence of content of his works on social and political situation, order of official authorities and subjective vision of life. We have shown the evolution of didactic publications of A. Vvedens’ky and defined their place in the educational process in the secondary and higher school. His educational publications of Russian and Western European history and special historical disciplines have been especially valued.